Penyisihan Kromium (Cr) Pada Limbah Cair Elektroplating Menggunakan Biomassa Ragi Roti (Saccharomyces Cerevisiae) Yang Diimmobilisasi Dengan Kalsium Alginat - Masriza, Maya; Elystia, Shinta; Muria, Sri Rezeki (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Chromium (Cr) is a heavy metal that has a toxicity and the presence in waters caused by the disposal of wastewaste from various industrial activities, one of them is electroplating industry. One of method that can be applied to reduse the concentration of Cr in wastewater is biosorption using biomass of baker's yeast (Saccharomyces cerevisiae) which immobilization with calcium alginate. This research aims to determine the ability of biomass of baker's yeast (Saccharomyces cerevisiae) on variations concentration of sodium alginate (1%, 2% and 3%), weight biosorbent (0,5, 1, 1,5 and 2 grams) and contact time (1, 2, 3 and 4 hours). Concentration Cr wastewater was analyzed using AAS instrument. The results showed the Cr concentrations was highest at a concentration of 3% alginate, biosorbent weight of 0,5 gram and contact time of 3 hours with the adsorption capacity of 2,608 mg Cr /g biosorbent.Keywords: biosorption, Cr, electroplating wastewater, (Saccharomyces cerevisiae), Immobilization, calcium alginate.